Self-protection flux-cored wire for surfacing repair, preparation method of self-protection flux-cored wire and surfacing method
By adjusting the element components of the welding wire and the surfacing method, the problems of self-protection drug-based welding wire are easily cracked and costly are solved, and the high-performance and low-cost surfacing effect is achieved.
Patent Information
- Application Number
- CN202411348864.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
When existing self-protective pharmaceutical welding wires add inorganic minerals or ceramic oxides to the formulation to improve wear resistance, they lead to reduced weldability and prone to cracking, and contain rare earths and transition heavy metals, resulting in high costs.
Self-protected flux-core welding wire for surfacing repair consisting of iron tungsten powder, low-carbon ferrochromium powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, iron molybdenum powder, and silicon-manganese alloy powder. Through reasonable Adjust the element content and component ratio to prepare welding wires without inorganic minerals and ceramic oxides, and use specific surfacing methods to improve welding performance.
The welding performance is optimized, the surfacing layer is not prone to cracking, has low cost, and does not contain expensive elements. The formed surfacing layer has good hardness and wear resistance.
Smart Images

Figure CN119159280A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of welding, and in particular to cladding. Background Art
[0002] Modern heavy trucks and other heavy machinery parts, such as rotating shafts and large gears, are subject to wear and failure. With the increasing degree of automation in modern high-tech, the speed of such parts is faster and there is almost no time for "rest" or maintenance. This inevitably leads to faster and faster wear speed and degree, and even serious failure of local small-volume breakage and shedding under accidental accidents or erosion. The self-protective welding wire can be used to repair defective parts or prepare composite parts through the surfacing process, which can maintain the proper function of the parts while repairing or achieving the size of the parts. The structural surfacing layer formed by this type of welding wire needs to meet the following requirements: high hardness to maintain the wear resistance of the part material itself; the surfacing layer can be metallurgically combined with more base parts, and it is not easy to break at the interface after durability; the surfacing layer has high toughness and can form a sufficiently thick structure without cracking, which affects its application range; the welding wire needs to have good weldability, no spatter, continuous arc, and the surfacing layer formed has no pores and good appearance; the cost of the welding wire is low, reducing the use of rare earth and transition heavy metals.
[0003] At present, for the purpose of wear resistance or self-protection, sufficient inorganic minerals or ceramic oxides are added to the formula of self-shielded flux welding wire, which results in a lack of weldability and is prone to cracking after the cladding reaches a certain thickness, thus reducing the application range of the welding wire. Or hard metal compounds such as tungsten carbide and chromium carbide are directly added to the formula, and the proportion of high-carbon ferrochrome used is very high (>50%), and rare earth metals are also used as protective agents. These raw materials will greatly increase the cost of welding wire. Summary of the invention
[0004] The embodiments of the present application provide a self-shielded flux-cored welding wire and a surfacing method for surfacing repair, so as to solve the technical problems of easy cracking and high cost of the self-shielded flux-cored welding wire.
[0005] In the first aspect, an embodiment of the present application provides a self-shielded flux-cored welding wire for cladding repair. The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following elements, measured by mass percentage of the flux of the self-shielded flux-cored welding wire for cladding repair: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
[0006] In some embodiments of the present application, the flux of the self-shielded flux-cored welding wire for surfacing repair comprises the following components:
[0007] Tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder, iron powder.
[0008] In some embodiments of the present application, the content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or,
[0009] The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or,
[0010] The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or,
[0011] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or,
[0012] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or,
[0013] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0014] In some embodiments of the present application, the flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials, measured by mass percentage of the flux of the self-shielded flux-cored welding wire for cladding repair: 1.8% to 2.2% of tungsten iron powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
[0015] In a second aspect, an embodiment of the present application provides a method for preparing a self-shielded flux-cored welding wire for cladding repair, the method for preparing a self-shielded flux-cored welding wire for cladding repair comprising the following steps:
[0016] Provide metal powder raw materials;
[0017] The metal powder raw material is used as flux to prepare a flux-cored welding wire to obtain a self-protected flux-cored welding wire for cladding repair.
[0018] Among them, the metal powder raw material is composed of the following elements, measured by mass percentage: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
[0019] In some embodiments of the present application, the providing of metal powder raw material comprises the following steps:
[0020] Mix tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder and iron powder.
[0021] In some embodiments of the present application, the content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or,
[0022] The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or,
[0023] The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or,
[0024] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or,
[0025] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or,
[0026] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0027] In some embodiments of the present application, the metal powder raw material is composed of the following raw materials, measured in percentage by mass: 1.8% to 2.2% of ferrotungsten powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
[0028] In some embodiments of the present application, the particle size of the metal powder raw material is not greater than 250 um.
[0029] In a third aspect, an embodiment of the present application provides a surfacing method, wherein the surfacing method is performed by the self-shielding flux-cored welding wire for surfacing repair described in any embodiment of the first aspect, or by the self-shielding flux-cored welding wire for surfacing repair prepared by the method described in any embodiment of the second aspect,
[0030] Among them, the surfacing voltage is 32~34V,
[0031] The surfacing current is 300~350A.
[0032] The surfacing speed is 30-40cm / min.
[0033] The stem extension is 18 to 22 mm.
[0034] The state after welding is natural air cooling.
[0035] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0036] The self-shielded flux-cored welding wire for surfacing repair provided in the embodiment of the present application has excellent welding performance, and does not contain inorganic minerals and ceramic oxides, and the surfacing layer formed by surfacing thereof is not easy to crack; at the same time, it does not contain expensive elements such as rare earth and Nb, and the cost is relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0039] Figure 1 This is a photo of the appearance of the cladding wear-resistant test sample corresponding to Example 1 of the present application;
[0040] Figure 2 A cross-sectional photograph of the cladding wear-resistant test specimen corresponding to Example 1 of the present application;
[0041] Figure 3 This is a photo of the appearance of the cladding cracking test specimen corresponding to Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0043] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0045] Existing self-shielding flux welding wires have technical problems of easy cracking and high cost.
[0046] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0047] In the first aspect, an embodiment of the present application provides a self-shielded flux-cored welding wire for cladding repair. The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following elements, measured by mass percentage of the flux of the self-shielded flux-cored welding wire for cladding repair: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
[0048] The functions of each element in the self-shielded flux-cored welding wire for surfacing repair are as follows:
[0049] Carbon is an austenite-forming element and has important strengthening and deoxidation effects, but it is obviously brittle and also reduces the impact toughness of the material. It is necessary to control its ratio with other transition metals and the form of addition.
[0050] Chromium can produce solid solution strengthening and is the main element for the formation of hard phases such as carbides, but too high a content will affect the impact toughness of the cladding layer.
[0051] Molybdenum is a carbide-forming element. The solid solution and carbides formed are distributed in the cladding metal structure, which is beneficial to improve the hardness of the cladding layer, refine the metal grains, and improve the toughness of the cladding layer. However, too much Mo can hinder the diffusion of carbon and inhibit the chemical process of C and other elements.
[0052] Tungsten can increase the hardenability of the cladding layer, produce solid solution strengthening, and inhibit temper brittleness. The appropriate addition is beneficial to the improvement of impact toughness. It is also one of the important elements to improve the high temperature stability of the material.
[0053] Silicon is a strong ferrite-forming element that improves solid solution strengthening and has a deoxidizing effect, reducing the oxygen content in the weld. Combining it with manganese for deoxidation, it can make large particles of low-melting-point oxides in the weld overlay easier to float, thereby reducing the adverse effects of oxygen on the weld metal.
[0054] Manganese can improve hardenability and has good deoxidation and desulfurization effects. The combined effect of manganese and silicon is beneficial to reduce the oxygen content in the weld and improve the weld's resistance to thermal cracking. However, too much Mn will coarsen the material grains, reduce ductility, and reduce toughness.
[0055] Nickel can maintain high strength of the cladding layer while maintaining high toughness and can also improve a certain degree of corrosion resistance.
[0056] Boron is an important alloying element, which can also improve the amorphous forming ability of the cladding layer. The appropriate ratio can inhibit crystallization and make the grains finer. It is also a deoxidizer, which can reduce pores, stabilize the arc and reduce spatter.
[0057] Aluminum has a strong binding force with oxygen and can deoxidize and denitrify. When it reaches a certain value, it can significantly inhibit the formation of pores, stabilize the arc, and reduce the generation of welding smoke, but it may reduce the hardness.
[0058] Magnesium can deoxidize and denitrify, and can also improve the fluidity of the welding melt and improve its appearance.
[0059] The present application reasonably limits the content range of the above elements, and can obtain a self-shielded flux-cored welding wire for cladding repair with excellent welding performance.
[0060] The self-shielded flux-cored welding wire for surfacing repair provided in the present application has excellent welding performance, and does not contain inorganic minerals and ceramic oxides, and the surfacing layer formed by surfacing is not easy to crack; at the same time, it does not contain expensive elements such as rare earth and Nb, and the cost is relatively low.
[0061] In some embodiments of the present application, the flux of the self-shielded flux-cored welding wire for surfacing repair comprises the following components:
[0062] Tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder, iron powder.
[0063] The above components are all cheap, readily available and easy to process raw materials.
[0064] In some embodiments of the present application, the content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or,
[0065] The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or,
[0066] The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or,
[0067] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or,
[0068] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or,
[0069] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0070] In some embodiments of the present application, the flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials, measured by mass percentage of the flux of the self-shielded flux-cored welding wire for cladding repair: 1.8% to 2.2% of tungsten iron powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
[0071] In a second aspect, an embodiment of the present application provides a method for preparing a self-shielded flux-cored welding wire for cladding repair, the method for preparing a self-shielded flux-cored welding wire for cladding repair comprising the following steps:
[0072] S1: Provide metal powder raw materials;
[0073] S2: using the metal powder raw material as flux to prepare a flux-cored welding wire to obtain a self-shielded flux-cored welding wire for cladding repair,
[0074] Among them, the metal powder raw material is composed of the following elements, measured by mass percentage: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
[0075] Those skilled in the art can prepare flux-cored welding wire using the metal powder raw material as flux by methods known in the art, such as drawing method and extrusion method.
[0076] In some embodiments of the present application, the providing of metal powder raw material comprises the following steps:
[0077] Mix tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder and iron powder.
[0078] In some embodiments of the present application, the content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or,
[0079] The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or,
[0080] The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or,
[0081] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or,
[0082] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or,
[0083] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0084] In some embodiments of the present application, the metal powder raw material is composed of the following raw materials, measured in percentage by mass: 1.8% to 2.2% of ferrotungsten powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
[0085] In some embodiments of the present application, the particle size of the metal powder raw material is not greater than 250 um.
[0086] The particle size of the metal powder raw material can be adjusted by sieving.
[0087] In a third aspect, an embodiment of the present application provides a surfacing method, wherein the surfacing method is performed by the self-shielding flux-cored welding wire for surfacing repair described in any embodiment of the first aspect, or by the self-shielding flux-cored welding wire for surfacing repair prepared by the method described in any embodiment of the second aspect,
[0088] Among them, the surfacing voltage is 32~34V,
[0089] The surfacing current is 300~350A.
[0090] The surfacing speed is 30-40cm / min.
[0091] The stem extension is 18 to 22 mm.
[0092] The state after welding is natural air cooling.
[0093] It is easy to understand that the above-mentioned surfacing welding conditions can make the surfacing layer obtained by surfacing welding have good performance.
[0094] The surfacing method is implemented based on the self-shielded flux-cored welding wire for surfacing repair described in any embodiment of the first aspect, or the self-shielded flux-cored welding wire for surfacing repair prepared by the method described in any embodiment of the second aspect. The specific implementation of the surfacing method can refer to the above embodiments and common knowledge in the field. Since the surfacing method adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.
[0095] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0096] Example 1
[0097] This embodiment provides a self-shielded flux-cored welding wire for cladding repair, wherein the flux of the self-shielded flux-cored welding wire for cladding repair comprises the following components:
[0098] The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials in terms of mass percentage: 1.8% ferrotungsten powder, 20% low-carbon ferrochrome powder, 1.8% boron carbide powder, 1.5% ferrosilicon powder, 4.5% nickel powder, 0.2% aluminum-magnesium alloy powder, 3.5% ferromolybdenum powder, 0.2% silicon-manganese alloy powder, and the balance is iron powder.
[0099] The steel strip of the self-shielded flux-cored welding wire for surfacing repair is a cold-rolled low-carbon steel strip with a size of 0.3mm×14mm. Calculated by mass percentage of the steel strip, the constituent elements of the steel strip are 0.1% C, 0.5% Mn, 0.02% P, 0.003% S, 0.05% Si, and the balance is Fe.
[0100] The filling rate of the self-shielded flux-cored welding wire for surfacing repair is 45%.
[0101] The content of W in the ferrotungsten powder is 75%, and the balance is Fe.
[0102] The low-carbon ferrochrome powder contains 0.25% C, 60% chromium and the remainder Fe.
[0103] The content of Si in the ferrosilicon powder is 85%, and the balance is Fe.
[0104] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg.
[0105] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe.
[0106] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0107] Example 2
[0108] This embodiment provides a self-shielded flux-cored welding wire for cladding repair, wherein the flux of the self-shielded flux-cored welding wire for cladding repair comprises the following components:
[0109] The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials, measured by mass percentage: 2.2% of tungsten iron powder, 24% of low-carbon ferrochrome powder, 2.2% of boron carbide powder, 2% of ferrosilicon powder, 5.2% of nickel powder, 0.3% of aluminum-magnesium alloy powder, 4.5% of ferromolybdenum powder, 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
[0110] The steel strip of the self-shielded flux-cored welding wire for surfacing repair is a cold-rolled low-carbon steel strip with a size of 0.3mm×14mm. Calculated by mass percentage of the steel strip, the constituent elements of the steel strip are 0.1% C, 0.5% Mn, 0.02% P, 0.003% S, 0.05% Si, and the balance is Fe.
[0111] The filling rate of the self-shielded flux-cored welding wire for surfacing repair is 45%.
[0112] The content of W in the ferrotungsten powder is 75%, and the balance is Fe.
[0113] The low-carbon ferrochrome powder contains 0.25% C, 60% chromium and the remainder Fe.
[0114] The content of Si in the ferrosilicon powder is 85%, and the balance is Fe.
[0115] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg.
[0116] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe.
[0117] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0118] Example 3
[0119] This embodiment provides a self-shielded flux-cored welding wire for cladding repair, wherein the flux of the self-shielded flux-cored welding wire for cladding repair comprises the following components:
[0120] The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials in terms of mass percentage: 2% ferrotungsten powder, 22% low-carbon ferrochromium powder, 2% boron carbide powder, 1.8% ferrosilicon powder, 5% nickel powder, 0.25% aluminum-magnesium alloy powder, 4% ferromolybdenum powder, 0.25% silicon-manganese alloy powder, and the balance is iron powder.
[0121] The steel strip of the self-shielded flux-cored welding wire for surfacing repair is a cold-rolled low-carbon steel strip with a size of 0.3mm×14mm. Calculated by mass percentage of the steel strip, the constituent elements of the steel strip are 0.1% C, 0.5% Mn, 0.02% P, 0.003% S, 0.05% Si, and the balance is Fe.
[0122] The filling rate of the self-shielded flux-cored welding wire for surfacing repair is 45%.
[0123] The content of W in the ferrotungsten powder is 75%, and the balance is Fe.
[0124] The low-carbon ferrochrome powder contains 0.25% C, 60% chromium and the remainder Fe.
[0125] The content of Si in the ferrosilicon powder is 85%, and the balance is Fe.
[0126] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg.
[0127] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe.
[0128] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0129] Comparative Example 1
[0130] This embodiment provides a self-shielded flux-cored welding wire for cladding repair, wherein the flux of the self-shielded flux-cored welding wire for cladding repair comprises the following components:
[0131] The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials in terms of mass percentage: 2% ferrotungsten powder, 22% low-carbon ferrochrome powder, 2% boron carbide powder, 4% Ferrosilicon powder, 8% Nickel powder, 0.25% aluminum-magnesium alloy powder, 6% Ferromolybdenum powder, 1% of silicon-manganese alloy powder and the balance is iron powder.
[0132] The steel strip of the self-shielded flux-cored welding wire for surfacing repair is a cold-rolled low-carbon steel strip with a size of 0.3mm×14mm. Calculated by mass percentage of the steel strip, the constituent elements of the steel strip are 0.1% C, 0.5% Mn, 0.02% P, 0.003% S, 0.05% Si, and the balance is Fe.
[0133] The filling rate of the self-shielded flux-cored welding wire for surfacing repair is 45%.
[0134] The content of W in the ferrotungsten powder is 75%, and the balance is Fe.
[0135] The low-carbon ferrochrome powder contains 0.25% C, 60% chromium and the remainder Fe.
[0136] The content of Si in the ferrosilicon powder is 85%, and the balance is Fe.
[0137] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg.
[0138] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe.
[0139] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0140] Comparative Example 2
[0141] This embodiment provides a self-shielded flux-cored welding wire for cladding repair, wherein the flux of the self-shielded flux-cored welding wire for cladding repair comprises the following components:
[0142] The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials in terms of mass percentage of the flux of the self-shielded flux-cored welding wire for cladding repair: 4% Tungsten iron powder, 30% Low carbon ferrochrome powder, 2% boron carbide powder, 4% Ferrosilicon powder, 8% Nickel powder, 0.65% Aluminum-magnesium alloy powder, 6% ferromolybdenum powder, 0.2% silicon manganese alloy powder, and the balance is iron powder.
[0143] The steel strip of the self-shielded flux-cored welding wire for surfacing repair is a cold-rolled low-carbon steel strip with a size of 0.3mm×14mm. Calculated by mass percentage of the steel strip, the constituent elements of the steel strip are 0.1% C, 0.5% Mn, 0.02% P, 0.003% S, 0.05% Si, and the balance is Fe.
[0144] The filling rate of the self-shielded flux-cored welding wire for surfacing repair is 43%.
[0145] The content of W in the ferrotungsten powder is 75%, and the balance is Fe.
[0146] The low-carbon ferrochrome powder contains 0.25% C, 60% chromium and the remainder Fe.
[0147] The content of Si in the ferrosilicon powder is 85%, and the balance is Fe.
[0148] The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg.
[0149] The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe.
[0150] The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
[0151] Related experiments and effect data:
[0152] After surface grinding, cleaning and rust removal of the No. 45 steel plate, the base plate is made for surfacing welding. The self-protective flux-cored welding wire for surfacing repair provided in Example 1 is continuously surfacing welded along one end of the base plate in a longitudinal direction, and then the second layer is surfacing welded after cooling. Each layer is surfacing welded for 8 to 10 passes. The thickness of the final surfacing layer is about 5 mm and the area is about 50 square centimeters. A surfacing wear-resistant test sample is obtained. The surfacing layer of the surfacing wear-resistant test sample is tested for hardness and wear resistance. Subsequently, the self-protective flux-cored welding wire for surfacing repair provided in Example 2, Example 3, Comparative Example 1, and Comparative Example 2 are used to replace the self-protective flux-cored welding wire for surfacing repair provided in Example 1 to prepare the surfacing layer of the surfacing wear-resistant test sample, and the surfacing layer of the obtained surfacing wear-resistant test sample is tested for hardness and wear resistance.
[0153] After surface grinding, cleaning and rust removal of the No. 45 steel plate, the bottom plate is made for surfacing. The self-shielding flux-cored welding wire for surfacing repair provided in Example 1 is continuously surfacing along one end of the bottom plate in a longitudinal direction, and then the next layer is surfacing after cooling. A total of 4 to 5 layers are surfacing, and each layer is surfacing 8 to 10 passes. The thickness of the final surfacing layer is about 20 mm and the area is about 50 square centimeters. A surfacing crack test specimen is obtained. The surfacing layer of the surfacing crack test specimen is tested for cracking. The surfacing layer of the surfacing crack test specimen is prepared by replacing the self-shielding flux-cored welding wire for surfacing repair provided in Example 1 with the self-shielding flux-cored welding wire for surfacing repair provided in Example 2, Example 3, Comparative Example 1, and Comparative Example 2, and the surfacing layer of the obtained surfacing crack test specimen is tested for cracking.
[0154] The above-mentioned surfacing processes are all implemented with the following parameters: surfacing voltage is 34V, surfacing current is 300A, surfacing speed is 35cm / min, dry extension is 20mm, and the post-welding state is natural air cooling.
[0155] The hardness test includes Rockwell hardness test and Vickers hardness test. The Rockwell hardness test is carried out by TH-320 Rockwell hardness tester.
[0156] The Vickers hardness test is performed as follows:
[0157] After the weld overlay wear test specimen was wire cut, ground and polished, the load was 300 grams and the loading time was 15 seconds. The Vickers hardness of the cross section was measured at intervals of 300 microns, with 100 microns outside the interface between the substrate and the weld overlay layer as the first point.
[0158] Hardness test data is shown in Table 1:
[0159] Table 1 Hardness test data of surfacing wear-resistant test specimens corresponding to Examples 1 to 5
[0160] HRC <![CDATA[HV 0.3 ]]> Example 1 60.08 1072.5 Example 2 60.91 1223.2 Example 3 60.44 1147.1 Comparative Example 1 36.21 518.5 Comparative Example 2 62.26 1165.32
[0161] It can be seen from Table 1 that the Rockwell hardness and Vickers hardness values of the surfacing wear-resistant test specimens corresponding to Examples 1 to 3 and Comparative Example 2 are both higher, while those of Comparative Example 1 are lower.
[0162] The wear resistance test is carried out as follows:
[0163] Each weld overlay layer was subjected to rotational dry friction at room temperature, with a load of 1 kg, a wear time of 20 minutes, a wear rotation radius of 2 mm, and a rotation speed of 1300 rpm, and wear data was collected.
[0164] Wear data is shown in Table 2:
[0165] Table 2 Wear data of cladding wear-resistant test specimens corresponding to Examples 1 to 5
[0166] Friction coefficient <![CDATA[Wear volume (mm 3 )]]> <![CDATA[Wear rate (mm 3 / Nm)]]> Example 1 0.48 <![CDATA[10.02×10 -3 ]]> <![CDATA[3.41×10 -6 ]]> Example 2 0.51 <![CDATA[12.08×10 -3 ]]> <![CDATA[4.15×10 -6 ]]> Example 3 0.49 <![CDATA[11.26×10 -3 ]]> <![CDATA[3.86×10 -6 ]]> Comparative Example 1 0.43 <![CDATA[154.3×10 -3 ]]> <![CDATA[52.9×10 -6 ]]> Comparative Example 2 0.50 <![CDATA[69.32×10 -3 ]]> <![CDATA[23.49×10 -6 ]]>
[0167] It can be seen from Table 2 that the wear resistance of the surfacing wear-resistant test specimens corresponding to Examples 1 to 3 is very excellent, and the wear rate is very low. Comparative Examples 1 to 2 are much lower than Examples 1 to 3, and Comparative Example 1 has the lowest wear resistance.
[0168] The cracking test is carried out as follows:
[0169] After grinding and polishing the weld overlay crack test specimen, load 1 kg under a microhardness tester for 30 seconds to form a "cross" indentation on the surface. Observe under an electron microscope to see if there are obvious extended cracks.
[0170] No obvious extended cracks were observed on the cladding crack test specimens corresponding to Examples 1 to 3 and Comparative Example 1. This shows that the cladding layers of the cladding crack test specimens corresponding to Examples 1 to 3 and Comparative Example 1 have good crack resistance. However, the cladding layer of the cladding crack test specimen corresponding to Comparative Example 2 has poor slag removal and poor appearance, so the test cannot be carried out and has no practical value. The appearance photo of the cladding crack test specimen corresponding to Comparative Example 2 is shown in Figure 2. Figure 3 .
[0171] In general, the cladding layers formed in Examples 1 to 3 all exhibit good hardness, wear resistance and crack resistance. However, the hardness and wear resistance of Comparative Example 1 are poor, but the crack resistance is acceptable. This may be because molybdenum and nickel elements improve the toughness of the cladding layer by refining the ferrite structure and are not easy to crack. However, excessive use or imbalance with other strengthening elements may inhibit the combination of strengthening elements and hinder the diffusion of carbon and boron, thereby rapidly reducing the amount of hard phase in the cladding layer. Therefore, the hardness and wear resistance of the cladding layer will also significantly decrease with the reduction of hard phase. The excessive silicon-manganese ratio makes the grains of the cladding layer begin to become coarse, which also has a negative effect on the performance. The hardness and wear resistance of Comparative Example 2 are better, but the crack resistance is poor. This may be because compared with Comparative Example 1, the ratio of strengthening elements chromium and tungsten is increased to increase the content of hard phases such as tungsten carbide or chromium carbide in the surfacing layer to maintain hardness and wear resistance, but at the same time more deoxidizing elements are needed to maintain deoxidation and slag removal. However, light metal elements such as aluminum and magnesium used for deoxidation will quickly reduce the toughness of the surfacing layer, resulting in cracking that is very easy to occur, and excessive aluminum and magnesium will seriously reduce the surface state of the surfacing layer, and even result in an incomplete surfacing surface appearance.
[0172] In addition, during the above-mentioned surfacing process of the self-shielded flux-cored welding wire for surfacing repair provided in Examples 1 to 3, the smoke generated was very small, and there was no arc breaking. Visually observing the appearance of the final surfacing layer formed, the welding spatter particles were very small, there were no visible cracks and obvious slag sticking. The slag began to be dark black and evenly covered the surface of the surfacing layer. It would fall off by itself after cooling. Finally, the entire surfacing metal surface showed a faint red color, which was smooth, bright and beautiful, and was an acceptable morphology in practical applications. The appearance photo of the surfacing wear-resistant test sample corresponding to Example 1 is shown in the figure below. Figure 1 As shown by Figure 1 It can be seen that the morphology of the surface of the cladding layer is in good condition. After cutting, grinding, corroding and cleaning the cladding wear-resistant test sample corresponding to Example 1, the cross section of the cladding layer is observed. Figure 2 As shown, the thickness of the cladding layer is about 4-5 mm. Through scanning electron microscopy, there is an obvious plane transition layer between the cladding layer and the base plate, with a thickness of about 15 microns, indicating that the cladding layer is well bonded to the substrate and presents a stable metallurgical bonding state.
[0173] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0174] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.
[0175] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A self-shielded flux-cored welding wire for cladding repair, characterized in that: The flux of the self-shielded flux-cored welding wire for surfacing repair is composed of the following elements in percentage by mass: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
2. The self-shielded flux-cored welding wire for cladding repair according to claim 1, characterized in that: The flux of the self-shielded flux-cored welding wire for surfacing repair comprises the following components: Tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder, iron powder.
3. The self-shielded flux-cored welding wire for cladding repair according to claim 2, characterized in that: The content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or, The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or, The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or, The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or, The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or, The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
4. The self-shielded flux-cored welding wire for cladding repair according to claim 3, characterized in that: The flux of the self-shielded flux-cored welding wire for cladding repair is composed of the following raw materials in terms of mass percentage: 1.8% to 2.2% of ferrotungsten powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
5. A method for preparing a self-shielded flux-cored welding wire for surfacing repair, characterized in that: The preparation method of the self-protected flux-cored welding wire for surfacing repair comprises the following steps: Provide metal powder raw materials; The metal powder raw material is used as flux to prepare a flux-cored welding wire to obtain a self-protected flux-cored welding wire for cladding repair. Among them, the metal powder raw material is composed of the following elements, measured by mass percentage: 0.4% to 0.6% C, 1.31% to 1.72% B, 1.32% to 1.78% Si, 0.12% to 0.19% Mn, 0.12% to 0.18% Al, 0.08% to 0.12% Mg, 12.0% to 14.4% Cr, 2.1% to 2.7% Mo, 0.56% to 0.75% W, 4.5% to 5.4% Ni, and the balance is Fe.
6. The method for preparing the self-shielded flux-cored welding wire for cladding repair according to claim 5, characterized in that: The step of providing the metal powder raw material comprises the following steps: Mix tungsten iron powder, low carbon ferrochrome powder, boron carbide powder, ferrosilicon powder, nickel powder, aluminum-magnesium alloy powder, ferromolybdenum powder, silicon-manganese alloy powder and iron powder.
7. The method for preparing the self-shielded flux-cored welding wire for cladding repair according to claim 6, characterized in that: The content of W in the ferrotungsten powder is 75%, and the balance is Fe; and / or, The low carbon ferrochrome powder has a C content of 0.15% to 0.5%, a chromium content of 60%, and the balance of Fe; and / or, The Si content in the ferrosilicon powder is 85%, and the balance is Fe; and / or, The aluminum-magnesium alloy powder contains 62% Al and the remainder is Mg; and / or, The content of Mo in the ferromolybdenum powder is 60%, and the balance is Fe; and / or, The silicon-manganese alloy powder contains 64% Mn, 27% Si and the remainder Fe.
8. The method for preparing the self-shielded flux-cored welding wire for cladding repair according to claim 7, characterized in that: Measured in percentage by mass of the metal powder raw materials, the metal powder raw materials are composed of the following raw materials: 1.8% to 2.2% of tungsten iron powder, 20% to 24% of low-carbon ferrochrome powder, 1.8% to 2.2% of boron carbide powder, 1.5% to 2% of ferrosilicon powder, 4.5% to 5.2% of nickel powder, 0.2% to 0.3% of aluminum-magnesium alloy powder, 3.5% to 4.5% of ferromolybdenum powder, 0.2% to 0.3% of silicon-manganese alloy powder, and the balance is iron powder.
9. The method for preparing a self-shielded flux-cored welding wire for cladding repair according to claim 5, characterized in that: The particle size of the metal powder raw material is not greater than 250um.
10. A surfacing method, characterized in that: The surfacing method is performed by using the self-shielded flux-cored welding wire for surfacing repair as described in any one of claims 1 to 4, or by using the self-shielded flux-cored welding wire for surfacing repair prepared by the method described in any one of claims 5 to 9, Among them, the surfacing voltage is 32~34V, The surfacing current is 300~350A. The surfacing speed is 30-40cm / min. The stem extension is 18 to 22 mm. The state after welding is natural air cooling.
Citation Information
Patent Citations
Iron-based abrasion resistant overlaying-welding flux-cored wire
CN101670501A
A high boron iron-based wear-resistant flux-cored welding wire
CN102284806A
Flux-cored wire for coke-breaking roll overlaying welding
CN105414798A
High-strength and high-abrasion-resistance stainless steel surfacing flux-cored wire and application thereof
CN109048120A
Special flux-cored welding wire for deep-sea wet FCAW and preparation method therefor
WO2023160718A1
